Isolation, Characterization, and Complete Genome Sequence of Escherichia Phage KIT06 Which Infects Nalidixic Acid-Resistant Escherichia coli - Nguyen Song Han; Mana Harada; Nguyen Huan Pham-Khanh; Kaeko Kamei (MDPI AG, 2024)
Escherichia coli (E. coli) is one of the most common sources of infection in humans and animals. The emergence of E. coli which acquires resistance to various antibiotics has made treatment difficult. Bacteriophages can be considered promising agents to expand the options for the treatment of antibiotic-resistant bacteria. This study describes the isolation and characterization of Escherichia phage KIT06, which can infect E. coli resistant to the quinolone antibiotic nalidixic acid. Phage virions possess an icosahedral head that is 93 ± 8 nm in diameter and a contractile tail (116 ± 12 nm × 13 ± 5 nm). The phage was found to be stable under various thermal and pH conditions. A one-step growth curve showed that the latent time of the phage was 20 min, with a burst size of 28 particles per infected cell. Phage KIT06 infected 7 of 12 E. coli strains. It inhibited the growth of the host bacterium and nalidixic acid-resistant E. coli. The lipopolysaccharide and outer membrane proteins of E. coli, tsx and btuB, are phage receptors. Phage KIT06 is a new species of the genus Tequatrovirus with a genome of 167,059 bp consisting of 264 open reading frames (ORFs) that encode gene products related to morphogenesis, replication, regulation, and host lysis. The lack of genes encoding integrase or excisionase indicated that this phage was lytic. Thus, KIT06 could potentially be used to treat antibiotic-resistant E. coli using phage therapy. However, further studies are essential to understand its use in combination with other antimicrobial agents and its safe use in such applications.